Compensation, Technology Use, Work Stress, and Organisational Commitment Towards Gen Z's Turnover Intention - Herdiansyah, Sayyid; Suhardi; Firdaus, Rahmad (MANDAR: Management Development and Applied Research Journal, 2025)
This study examines the factors influencing turnover intention among Generation Z employees in Pangkalpinang, focusing on the roles of compensation, technology use, work stress, and organizational commitment. The rise of turnover among younger employees has created organizational instability, making it crucial to understand the determinants that shape their decision to remain or leave. Using a quantitative approach, data were collected from 110 Gen Z employees through a structured Likert-scale questionnaire, and the relationships among variables were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The findings show that work stress has a strong positive and significant effect on turnover intention, indicating that heightened psychological pressure directly increases employees’ desire to leave. Compensation and technology use significantly increase organizational commitment, yet neither variable shows a direct effect on turnover intention. Furthermore, organizational commitment does not mediate the influence of compensation, technology use, or work stress on turnover intention, suggesting that commitment is not a decisive psychological mechanism for employee retention among Generation Z. The study highlights the need for organizations to prioritize stress management, digital support systems, and workplace well-being strategies to reduce turnover. Future research is recommended to examine additional psychological and contextual variables that may better explain retention among younger workers